Numerical Study on the Influence of the Oscillating Surface Oxygen Concentration on the Bioconvection in a Two-Dimensional Deep Chamber - Masahide NAKAMURA; Yuusuke ISHIMI; Orie TAMURA; Wataru SUGIYAMA (Journal of Fluid Science and Technology, 2010)
Numerical study on the two-dimensional bioconvection in a deep chamber was carried out under the condition of the oscillating surface oxygen concentration to obtain the basic data for the control of bioconvection by using the surface oxygen concentration. As the numerical results in a large Γ region have an important meaning from a practical viewpoint, the numerical calculations were carried out within the range of 100000 ≤ Γ ≤ 500000, where Γ is a non-dimensional parameter that corresponds to the Rayleigh number in natural convection. The calculation results are summarized as follows. (1) The inactive zone where the bacteria do not swim actively is formed near the bottom of chamber. (2) The oscillating surface oxygen concentration has an effect to enhance the cell sedimentation. (3) The enhancement of the cell sedimentation due to the oscillating surface oxygen concentration becomes remarkable with the decrease in Γ.